Bilateral Peritonsillar Abscess in an Infant: An Unusual Presentation of Sore Throat - Mariana Manzoni Seerig; Letícia Chueiri; Janaina Jacques; Maria Fernanda Piccoli Cardoso de Mello; Martin Batista Coutinho da Silva; Daniel Buffon Zatt; Rosana Cristine Otero Cunha; Andre Souza de Albuquerque Maranhão (Case Reports in Otolaryngology)
Introduction. Peritonsillar abscess is considered a suppurative complication of acute tonsillitis. It is usually unilateral and clinically evident bilateral presentation is uncommon. The condition affects mainly children older than 10 years and young adults. Herein we present a rare case of bilateral peritonsillar abscess in an infant. Presentation of Case. A 1-year-old boy presented with a two-day history of worsening sore throat, loss of appetite, vomiting, and fever. Examination of the oral cavity and oropharynx revealed enlarged and inflamed tonsils and a bilaterally congested and bulging soft palate. CT scan confirmed the hypothesis of bilateral peritonsillar abscess. Antibiotic therapy was instituted and after 5 days only slight regression of swelling of the soft palate was observed. He underwent a surgical procedure for draining the abscesses. After the procedure, he presented good clinical and laboratory evolution and was discharged home. Discussion. Although peritonsillar abscesses are considered common complications of acute tonsillitis bilateral cases are extremely rare, especially in early childhood. The diagnosis is based on history and physical examination and the treatment remains controversial among otolaryngologists. Conclusion. Bilateral peritonsillar abscess should be diagnosed and treated promptly and adequately to prevent respiratory obstruction and to avoid dissemination into the deep neck spaces.